Spatial scaling of protected area influences on human demography and livelihoods in Botswana. (8th April 2014) - GUPTA, A. CLARE
SUMMARY: A growing body of 'people and parks' literature examines the interactions between protected areas (PAs) and people who live around them. This study of Chobe National Park (Botswana), which has one of the largest concentrations of wildlife in Africa, highlights a PA's influence beyond its buffer zone and provides a more detailed understanding of the complex dynamics within a PA buffer. Overall net population growth in the areas adjacent to Chobe National Park (hereafter referred to as the 'buffer' area) does not preclude outmigration from certain Park buffer areas where declining agricultural opportunities have pushed working-age residents in search of work to urban areas around and beyond the Park. At the same time, skilled workers have moved to some of these rural Park buffer villages to take advantage of new civil service positions. The PA also influences long-time rural dwellers' social and economic exchanges with urban kin and exacerbates dependence relations, placing economic strain upon urban migrants. In this way, the economic and social effects of PAs are neither uniform across their borders nor limited to those borders. These outcomes have important implications for biodiversity conservation in rural areas as they suggest that population growth may not be an accurate proxy for threats to biodiversity, if new and long-term residents come to rely on less resource-intensive livelihood practices.